SISTEM MANAJEMEN MUTU PADA PERGURUAN TINGGI - Juhana , Dudung (Majalah Bisnis & IPTEK, 2021)
A product can have a quality or in accordance with our quality standards that have been determined. Standardization of the quality of a product includes raw materials and finished goods quality. SSM application of ISO 9001:2008 for the quality of education can confirm its existence as one of the supporting unit must have a world-class qualification. Improved quality of service with reference to the international standards that are packed with quality management system (Quality Managment System) standard ISO 9001:2008 lead to a positive impact for college. Keywords: quality management system; college